Effect of Gestational Diabetes Mellitus on Gross Morphological Structure of Preterm Placenta (Bangladesh Journal of Anatomy, 2010)
Context: Preterm birth is the major cause of perinatal mortality and morbidity. For the last few decades, it has become an important issue in public health policies of developing countries. Gestational diabetes mellitus (GDM) is one of the high-risk factors for the preterm birth and altered fetal development. This pregnancy induced disorder leads to an increased level of all metabolic substances to the fetal circulation due to development of maternal insulin resistance. It imposes a heavy burden on the mother who is pregnant and these patients have a tendency toward metabolic instability. As there is an intimate relationship between the fetus and placenta, the present study aimed to observe the effect of this pregnancy induced disorder to the preterm placenta. Study design: The study was observational, analytical and cross sectional. Place and period of study: The study was carried out in the Department of Anatomy, BSMMU, Dhaka during the study period of January 2005 to December 2005. Materials and Methods: A total of forty-four samples were collected from women during 28 weeks to 36 completed weeks of gestation. Among them, twenty-two samples belonged to mothers having GDM and twenty-two belonged to normal pregnancy (control group). The placentas were examined to measure their diameter, thickness, cotyledons number, weight, and volume. Result: In this study, the GDM group showed significantly higher values for the variables of diameter, weight and volume. On the other hand, the thickness of the placenta showed lower values and cotyledons number showed higher values in GDM group but the result did not reach a significant level. Conclusion: The findings in this study supported that the gross morphological structure of the placentas in GDM mother did not present any specific, constant or uniform pattern of abnormality. Therefore, it is difficult to establish a clear cut correlation between the placental changes and diabetic state in the mother during pregnancy. However, increased placental weight, volume and diameter found in gestational diabetic mother have supported that these changes may be a long term compensatory mechanism, aiming to secure a sufficient nutrient supply to support the growth of large-for-gestational age (LGA) fetus. But the hormonal and metabolic abnormalities present in the diabetic mother and the fetus are important variables to be considered when studying the placenta. Key words: Preterm Placenta; GDM; Gross morphology. DOI: 10.3329/bja.v8i1.6107 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 34-38